The meta-ethical significance of experiments about folk moral objectivism. (18th August 2019) - Hopster, Jeroen
ABSTRACT: The meta-ethical commitments of folk respondents – specifically their commitment to the objectivity of moral claims – have recently become subject to empirical scrutiny. Experimental findings suggest that people are meta-ethical pluralists: There is both inter- and intrapersonal variation with regard to people's objectivist commitments. What meta-ethical implications, if any, do these findings have? I point out that current research does not directly address traditional meta-ethical questions: The methods used and distinctions drawn by experimenters do not perfectly match those of meta-ethicists. However, I go on to argue that, in spite of this mismatch, the research findings should be of interest to moral philosophers, including meta-ethicists. Not only do these findings extend the field of moral psychology with new data and hypotheses, but they also provide tentative evidence that touches on the adequacy of theses in moral semantics and moral metaphysics. Specifically, they put pressure on arguments in support of moral realism.